O Projeto de Educação Integral no Ceará: uma análise onto-marxista de seus fundamentos teórico-metodológicos, concepções e competências socioemocionais - Silva, Sirneto Vicente da (2023)
As a requirement for the offer of comprehensive education to high school students in the state of Ceará, the government implemented, in 2018, the Policy for the Development of Socioemotional Skills, in Portuguese "Política de Desenvolvimento das Competências Socioemocionais (PDCSE)". Understood as a complement to the teaching of cognitive skills, this policy is carried out through the mediation of the Class Director Teacher Project, in Portuguese "Projeto Professor Diretor de Turma (PPDT)" and the subjects Formation for Citizenship (FC) and Core Work, Research, and Social Practices, in Portuguese "Núcleo Trabalho, Pesquisa e Práticas Sociais (NTPPS)". Systematized by the Ayrton Senna Institute, a private capital company, the PDCSE is understood as fundamental to the education of students so that they are able to respond to the demands of the complex world scenario, given the constant transformations that have been taking place in the economic sector. This research aims to analyze the ongoing educational project in the state of Ceará, called Comprehensive Education, in order to identify the theoretical and methodological assumptions and conceptions of the education offered to students in public high schools, in the light of an Onto-Marxist analysis. It is divided into four specific objectives, which are: (a) to understand the foundations of Marxism for the analysis of the object of study, emphasizing the centrality of work as a complex that founds the social being and its role in the integral formation of the human being; (b) to examine the official documents that define the proposal of pedagogical work for the development of comprehensive education for high school students in Ceará; c) identify the conception of comprehensive education defined by the government of the state of Ceará, analyzing the foundations and the theoretical-methodological bases that support the Education Project of the state of Ceará; d) investigate the relationship between cognitive learning, development of socioemotional skills, and the discourse of offer of comprehensive education by the government of Ceará, aiming to understand the purpose of this formation model in the context of capitalist society. To do this, it takes as its method of analysis the historical-dialectical materialism of Marx and Engels, recovered by Lukács in his Ontology of Social Being, which contributes to the unveiling of the object as part of the social totality. It is based on theoreticalbibliographical research from authors who deal with the categories of work and its relation with the complexes of language and education, reproduction of capital, comprehensive education, structural crisis of capital, and competencies; and on documental research, through the analysis of the Comprehensive Education Project of Ceará. Our study points out that the Comprehensive Education Project of Ceará aims to prepare flexible and polyvalent individuals, so that they can adapt and/or passively accept the precarious conditions of work or non-work imposed by the capital in structural crisis; this education project corroborates the other policies and projects that are being developed in Ceará in order to form human capital; under the justification of offering equal educational opportunities, social and emotional competencies make students responsible for their academic and/or professional achievements. That said, education has been predominantly performing the function of reproducing the capitalist relations of production through a human formation aimed at responding to market demands under the tutelage of the State, through educational reforms, programs, and projects whose supposed objective is to implement a complete formation for students.